Pneumatic conveying design guide - Mills, David (Butterworth-Heinemann is an imprint of Elsevier, 2015)
Pneumatic Conveying Design Guide, 3rd Edition is divided into three essential parts, system and components, system design, and system operation, providing both essential foundational knowledge and practical information to help users understand, design, and build suitable systems. All aspects of the pneumatic conveying system are covered, including the type of materials used, conveying distance, system constraints, including feeding and discharging, health and safety requirements, and the need for continuous or batch conveying. This new edition also covers information on the other conveying systems available and compares them to this method. The existing content is brought up-to-date and the references are expanded and updated. This guide is an almost encyclopedic coverage of pneumatic conveying and as such is an essential text for both designers and users of pneumatic conveying systems. Each aspect of the subject is discussed from basic principles to support those new to, or learning about, this versatile technique
Includes index
Keywords: Pneumatic-tube transportation; Fleischqualität; Ernährung; Fleischverarbeitung; Fleisch; Pneumatische Förderanlage; Fleischer; Biochemie